Pengaruh Pariwisata Rafting terhadap Krama Tegal Kuning, Desa Bongkasa Pertiwi, Kecamatan Abiansemal, Kabupaten Badung - I Made Aryadha (UHN IGB Sugriwa Denpasar, 2018)
Tourism activities in Bali are very much in accordance with existing forms of tourism, such as cultural tourism, and so on. At the end of this tourism activity directed toward the pedesan in order to form Village Tourism and Tourism Village, rafting tourism activities called rafting has been touched and done by businessmen in the field of tourism and also communities who know the opportunities. This tourism gives influence or social impact to society around it, its influence tends to positive.